Structure and Thermal Property of Poly(R,S)-B-Hydroxybutyrate Synthesized by Aluminoxane Catalyst. - I Made Arcana (Journal of Mathematical and Fundamental Sciences, 2000)
Abstract. Poly(R,S)-B-hydroxybutyrate (PHB) was synthesized by ring-opening polymerization of racemic (R,S)-B-butyrolactone using tetraisobutyldialuminoxane (TIBAO) as catalyst. In previous studies, some factors or polymerization conditions such as polymerization suhue, polymerization time, nature of solvent, catalyst concentration, and modification of the catalyst system by water addition were varied to obtain optimal polymerization-results based on yield and molecular weight of polymers obtained. This study was emphasized on characterization of polymer by 13C NMR spectroscopy and Differential Scanning Calorimetry (DSC) to obtain informations about chemical structure and thermal properties of polymer obtained using tetraisobutyldialuminoxane catalyst. These analyses showed that tetraisobutyldialuminoxane catalyst produced partially stereoregular polymer depending on the quantity of water added to TIBAO catalyst. Extraction of polymer with acetyl-acetone (AcAc) or acetone separated the polymer into a soluble atactic fraction with amorphous structure and an insoluble isotactic fraction with crystalline structure. Addition of a certain quantity of water to the catalyst and treatment of polymer by solvent extraction have resulted in an increase in stereoregularity and crystallinity of polymer.